Pengembangan Aplikasi Layanan Pengaduan Masyarakat Untuk Dinas Kependudukan Dan Pencatatan Sipil Kota Pasuruan Berbasis Android - Hammer Zoelfagar Mahdias; Himawat Aryadita; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
TheiDepartement ofiPopulation andiCivil Registration (Dispendukcapil) of Pasuruan Cityiis an element of the implementation of the Regional Government of Pasuruan City in providing services in the field of Populationiand Civil Registry to the people of Pasuruan City which is required to improve the services, one of them is provide comfort to the community in expressing opinions or complaints experienced. So far, the handling of public complaints in Dispendukcapil Pasuruan still manually apply a lot of time, energy and cost because the people of Pasuruan City are required to visit Dispendukcapil Pasuruan in complaining, while the management complaints by the Administration Officer in Dispendukcapil Pasuruan should record each complaint and then made a complaint report that Human Error may cause because its negligence may cause the complaint to be unprocessable. Based on the problem, it is necessary an application of Complaints Service Society based on Android in order to submit a complaint without having to come to Dispendukcapil Pasuruan, as well as providing a complaint management information system for Administration Officer. The development of this system using waterfall model where the system is tested using Validation Testing method and User Acceptance Testing. From the results of this study produce needs analysis, design, implementation and testing system. Test results on this system indicate that the system is running in accordance with expectations and able to facilitate reports of complaints for Pasuruan City People or management of complaints for Administration Officers.